Investigation of Physico-chemical Properties and Evaluation of the Sensory Attributes of Kithul (Caryota urens) Treacle to Determine the Adulteration - J. A. A. C. Wijesinghe; R. M. K. G. D. M. Rathnayake (Current Research in Agricultural and Food Science Vol. 5, 2021)
Kithul treacle is a highly consumed traditional sweetener in Sri Lanka, not only for its taste but also for its nutritional value and health benefits. Consequently, Kithul treacle has been a target of adulteration by adding table sugar, which spoils the good recognition as low GI sweeteners. Due to the different types of adulteration as well as since there are no proper analytical methods identified to detect adulterations, its authentication has been challenging. This study focused on developing proper analytical methods to detect adulteration of Kithul treacle by table sugar. Pure Kithul treacle was collected from three geographical areas (Matale, Kandy, and Rathnapura) from registered tappers under the Ministry of export agriculture and that samples were adulterated with table sugar syrup at different concentrations (5%, 10%, 15%, 20%, and 25%). The samples were analyzed for physicochemical parameters and that test results the mean values of pH 5.58 while the free acidity was 0.33, Brix value was 69.36, moisture content was 23.52%, Electrical conductivity 474.22, and reducing sugar 68.81 for pure Kithul treacle. Results obtained from this study show all the parameters significantly different between pure and adulterated Kithul treacle and many of the commercial samples collected from local markets in the study area are of good quality and met the national and international standard limits. As codex Standard specifications for treacle, it should not contain more than 0.5% acidity and not more than 30% of moisture content. All tested samples complied with mentioned two requirements. However, the physicochemical test results for some Kithul treacle samples collected from local markets had a higher level of certain parameters than recommended, showing that a certain level of adulteration is practiced by few traders.